1994
DOI: 10.1111/j.1365-2788.1994.tb00420.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatal intestinal obstruction in the mentally handicapped

Abstract: ABSTRACT. In a retrospective study of hospital records over a 50‐year period, data on 32 patients who died as a result of intestinal obstruction are presented and compared with comparison groups and national mortality statistics. There was a higher incidence and lower mean age at death of fatal intestinal obstruction compared with the total national population. The mean age at death significantly increased over the study period. Intestinal volvulus was a common cause of obstruction particularly in those with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 7 publications
2
22
0
2
Order By: Relevance
“…4 One of the difficulties in reviewing the literature on medical and surgical emergencies and sudden, unexpected death in Down syndrome is that many studies have analysed these problems in intellectually disabled individuals as a group without describing the specific situation for Down syndrome. 5,6 (This may explain some of the contradictory conclusions that have been reported.) For this reason, the following analysis will sometimes deal with the broader range of individuals with intellectual and developmental disabilities.…”
Section: Introductionmentioning
confidence: 84%
“…4 One of the difficulties in reviewing the literature on medical and surgical emergencies and sudden, unexpected death in Down syndrome is that many studies have analysed these problems in intellectually disabled individuals as a group without describing the specific situation for Down syndrome. 5,6 (This may explain some of the contradictory conclusions that have been reported.) For this reason, the following analysis will sometimes deal with the broader range of individuals with intellectual and developmental disabilities.…”
Section: Introductionmentioning
confidence: 84%
“…This is concerning as the wider literature has identified poorer results for abdominal surgery in people with cognitive impairment due to delayed diagnoses, operative technical errors, and increased risk of postoperative complications [64,91,92] and limited successes [41]. PWIDs have increased risks from anaesthesia, there are known intubation risks in people with Down syndrome [93], and the choice of anaesthesia agents [94].…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes cancers are detected late, as observed in a study exploring deaths through abdominal obstruction. Of the 32 patients observed, 2 patients with mild to moderate IDs were diagnosed late from intestinal obstruction, and both died DOI: 10.1159/000492077 from colorectal cancer [64], whilst another case study [63] found that 1 male patient with ID had died before a cancer diagnosis was made. The authors of this review found no systematic studies or evaluations unanimously indicating whether colorectal cancer was diagnosed late in PWIDs.…”
Section: Clinical Presentation and Treatmentmentioning
confidence: 99%
“…Only for mentally disabled individual intestinal volvulus is a common cause of intestinal obstruction. Jancar and Speller [4] reported that half of all obstructions in such patients are caused by intestinal volvulus. Here we describe two patients with mental disability who presented with distal bowel obstruction caused by cecal volvulus, and discuss the relationship between cecal volvulus and mental disability.…”
Section: Introductionmentioning
confidence: 98%